IMPLEMENTASI KONTAINER KANTOR UNTUK MENDUKUNG PROGRAM SINDULANG NETCONNECT SEBAGAI STASIUN WI-FI PUBLIK DAN RUANG KOMUNITAS DIGITAL - Irawati, Indrarini Dyah; Hadiyoso, Sugondo; Munadi, Rendy; Hertiana, Sofia Naning; Istikmal, Istikmal (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
The Sindulang Village community faces obstacles in internet access due to uneven network infrastructure. This challenge makes it difficult for residents to obtain the latest information which is a key factor in supporting economic progress, education, and community welfare in the area. These obstacles arise due to geographical conditions that are difficult to access and suboptimal regional structures, which cause significant obstacles in resource management and accessibility. The Telkom University, PT. Tigaresi Bangun Nusaperdana, and SMK Al Amah Sindulang community service teams together overcome these obstacles by building Sindulang NetConnect as a public Wifi station as an innovative answer to provide easy internet access while accelerating the digitalization process for the Sindulang Village Community. In addition, in order to develop the Teaching Factory (TeFa) at SMK Al Amah Sindulang, an office container was implemented as a means of producing a Wifi network that can be used by students to improve their skills and experience in the networking field. This implementation was carried out in 2 stages, where the first stage was the construction of an office container and public Wifi services and in the second year a digital community space would be developed. Based on the results of the questionnaire on 30 respondents, it showed that 93.3% strongly agreed with the implementation of office containers as public Wifi stations and TeFa facilities that provide benefits for the Sindulang Village Community and students of SMK AL Amah Sindulang.